Effects of nitrogen fertilizing on the 1000-grain weight of maize inbred lines - Hojka, Zdravko (Economics of Agriculture, 2010)
In this study the influences of three N fertilizers (urea = 46% N; calcium ammonium nitrate or CAN; ammonium sulphate) and their distribution (N-autumn; N-spring; N-50% autumn + 50% spring; N-33% autumn + 67% spring; N-100% spring based on N-min method test) on 1000-grain weight of two maize inbred lines (IL1 and IL2) were tested under conditions of Zemun Polje calcaric chernozem for three growing seasons (2001, 2002 and 2003) with aim of N fertilization optimization for seed-maize growing. The use of the N-min method test (N ranging from 17 to 35 kg ha-1, in dependence on the soil mineral nitrogen content), especially in years with lower precipitation sums, resulted in the highest increase in 1000–grain weight (3 2%) of observed maize inbred lines in relation to the control. The application of different forms of nitrogen did not result in statistically signifcant differences in 1000–grain weight of observed maize inbred lines.